the response to service marketing failure - الكعبي, نعمه شلبيه (Journal of Economics and Administrative Sciences, 2014)
Because of the tremendous changes in the business environment and significant growth in living standards, increased demand for services in general and about the realized practitioners in the field of service that traditional marketing strategies and models administrative based solutions to mono as the price alone does not lead to the desired outcomes with customers and even organizations as it does not apply always for the manufacture of their services unique . therefore , the need to learn marketing service order and a clear and critical to avoid failures in service and the marketing document to knowledge would avoid the organization that the failure in the delivery of service and enhances the desired response to fix it in a timely manner and contain the failures leading to improve the relationship with the customer .On this basis, embodies the main objective of this research to give a clear picture of the failure to Marketing Service Auto Maintenance ( Kia ) and ( Hyundai ) , response options and customers filed a complaint or not in cases of failure that you get . Researcher adopted the descriptive analytical approach in this research was to use Form questionnaire ( designed in the light of previous studies have been formulated and tested measure under scientific methods and statistically ) to the symptoms of the collection of data from a sample search of ( 60 ) members of the Nobel Car companies mentioned divided by (30 ) individuals per station maintenance follow each company in Baghdad have been selected random . process took place data processing statistical methods and using the system spss computerized and was the most prominent outcomes of the research twice the dimensions of service delivery , which includes the physical evidence and the behavior of employees who represent the intrinsic grounds for the failure of the service car maintenance as well as poor response to customer complaints and requires companies Find pushing workers placed in training programs in order to improve the handling of customers and satisfy their needs and desires and to provide facilities and place of comfort and resolve congestion on service delivery.